2014
DOI: 10.13189/nrc.2014.020402
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Potable Water Supply System in Rural Ethiopia: The Case of Gonji Kolela Woreda, West Gojjam Zone, Ethiopia

Abstract: In rural Ethiopia, although considerable efforts have been made to improve and expand access to potable water supply, many Ethiopian rural communities still suffer from lack of safe drinking water. This research work intends to assess the challenges of potable water supply in selected rural kebeles1 of Gonji Kolela woreda2 in Amhara National Regional State, Ethiopia. Survey findings of the research show that, of the total 292 sample respondents those who use hand dug well, developed spring and rope pump accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…Hailu et al [77] who investigated exclosure fields had much higher cation exchange capacity than neighboring open grazing lands, this could be due to the variations of clay and OM between the land use types. This finding is supported by Sinore and Doboch [82] and Kibret [43], who found that organic matter, in particular, improves soil CEC and that clay and organic colloids are related to soil CEC. This outcome is supported by Mekuria et al [81] assessment that the CEC was much higher in the enclosure than in the grazing field.…”
Section: Total Nitrogensupporting
confidence: 59%
See 1 more Smart Citation
“…Hailu et al [77] who investigated exclosure fields had much higher cation exchange capacity than neighboring open grazing lands, this could be due to the variations of clay and OM between the land use types. This finding is supported by Sinore and Doboch [82] and Kibret [43], who found that organic matter, in particular, improves soil CEC and that clay and organic colloids are related to soil CEC. This outcome is supported by Mekuria et al [81] assessment that the CEC was much higher in the enclosure than in the grazing field.…”
Section: Total Nitrogensupporting
confidence: 59%
“…Shannon diversity can range from zero for communities with just one kind to a considerable amount for communities with several species, each with a small number of individuals. Indicators of Shannon variety include strong > 3.0, medium (2.0-3.0), low (1.0-2.0), and very low (<1.0) [43].…”
Section: Vegetation Data Analysis 231 Species Diversitymentioning
confidence: 99%
“…The water service coverage (7.64%) of the town was lower than other towns like Dukem (98.5%; [ 17 ]) and Wolaita Sodo (68%; [ 9 ]), and a rural district in western Ethiopia (70%; [ 24 ]) forcing most of the households to use unprotected Nano River water without heat or chemical treatment and thereby suffer from waterborne diseases. This implies that immediate action should be taken by the administration of the town and other concerned bodies to improve water service and create awareness of the community to boil or treat water using Wuha agar (chlorine-based water treatment solution) and Bishan gari (aluminum sulfate and calcium hypochlorite solution).…”
Section: Discussionmentioning
confidence: 99%
“…Its rural water supply condition is dispersing and inadequate. This happens because of the country's economy, source identification problem, and population settlement [KIBRET, TULU 2014]. The country's current water access improves from time to time by different means.…”
Section: Introductionmentioning
confidence: 99%
“…The root causes are a lack of proper design, study, run, maintenance, and treatment. Source drying and nonseparated water use of animals and humans are also the other malfunctioning causes [KIBRET, TULU 2014].…”
Section: Introductionmentioning
confidence: 99%